Age-Dependent Association of TNFSF15/TNFSF8 Variants and Leprosy Type 1 Reaction - Fava, Vinicius M.; Sales-Marques, Carolinne; Alcaïs, Alexandre; Moraes, Milton O.; Schurr, Erwin (Frontiers in Immunology, 2017)
A current major challenge in leprosy control is the prevention of permanent disabilities. Host pathological inflammatory responses termed type 1 reaction (T1R) are a leading cause of nerve damage for leprosy patients. The environmental or inherited factors that predispose leprosy cases to undergo T1R are not known. However, studies have shown an important contribution of host genetics for susceptibility to T1R. We have previously identified variants encompassing the TNFSF15/TNFSF8 genes as T1R risk factors in a Vietnamese sample and replicated this association in a Brazilian sample. However, we failed to validate in Brazilian patients the strong association of TNFSF15/TNFSF8 markers rs6478108 and rs7863183 with T1R that we had observed in Vietnamese patients. Here, we investigated if the lack of validation of these variants was due to age-dependent effects on association using four independent population samples, two from Brazil and two from Vietnam. In the combined analysis across the four samples, we observed a strong association of the TNFSF15/TNFSF8 variants rs6478108, rs7863183, and rs3181348 with T1R (pcombined = 1.5E−05, pcombined = 1.8E−05, and pcombined = 6.5E−06, respectively). However, the association of rs6478108 with T1R was more pronounced in leprosy cases under 30 years of age compared to the global sample [odds ratio (OR) = 1.95, 95% confidence interval (CI) = 1.54–2.46, pcombined = 2.5E−08 versus OR = 1.46, 95% CI = 1.23–1.73, pcombined = 1.5E−05]. A multivariable analysis indicated that the association of rs6478108 with T1R was independent of either rs7863183 or rs3181348. These three variants are known regulators of the TNFSF8 gene transcription level in multiple tissues. The age dependency of association of rs6478108 and T1R suggests that the genetic control of gene expression varies across the human life span.